Amenable yarı gruplarda Folner dizilerinin ideal yakınsaklığı - Çakal, Burak (Bartın Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2021)
Tez altı bölümden oluşmaktadır. İlk bölümde genel bir literatür bilgisi verilmiştir. İkinci bölümde, temel kavramlardan bahsedilmiştir. Üçüncü bölümde, Folner dizilerinin I-yakınsaklık kavramı tanımlandı. Dördüncü bölümde, Folner dizilerinin I-asimptotik ?-istatistiksel denkliği kavramı verildi. Beşinci bölümde, Folner dizilerinin I-asimptotik lacunary istatistiksel denkliği kavramı verildi. Altıncı bölümde ise sonuç ve öneriler yer almaktadır.

This thesis includes six chapters. A general knowledge of literature is given in the first chapter. In the second chapter, basic notions are mentioned. In the third chapter, I-convergence of Folner sequences is defined. In the fourth chapter, the concept of I asymptotically ?-statistical equivalence of Folner sequences is given. In the fifth chapter, the idea of I asymptotically lacunary statistical equivalence of Folner sequences is given. In the last chapter, there are some results and suggestions.
Ideal convergence of Folner sequence on amenable semigroups
Keywords: Folner dizisi; Amenable yarı grup; İdeal yakınsaklık; Lacunary dizi; Folner sequence; Ideal convergence; Lacunary sequence